Simulation on the Effect of Temperature Inlet and Mass-Flowrate Variations to the Temperature Distribution in Single Pelet Thermal Reactor Core Title - Yusibani, Elin; Helmiza, Fitri; Fashbir, Fashbir; Permana, Sidik (Universitas Negeri Surabaya, 2021)
AbstractThis paper presents simulation on temperature distribution in two-dimensional laminar flow for single pelet thermal reactor with variation on temperature inlet and mass-flowrate. The OpenFoam platform (Simflow 3.1) has been used for the computational and numerical analysis. The simulation is carried out on a single pellet with an aspect ratio of 1.2. The variations in the mass velocity of the coolant flow are 10, 100 and 14.300 kg×s-1 with a constant coolant temperature of 552 K, and the variations of the input coolant temperature are 300, 552 and 1000 K with a constant mass-flowrate of 10 kg×s-1. The results obtained from the simulation show that for variations in the input coolant temperature of 300, 552 and 1000 K, the fuel temperature can be reduced respectively by 34, 26 and 14 K. At the fastest variation in the coolant mass-flowrate of 14.300 kg×s-1, the coolant temperature around the pellet rises by 396 K. The decrease in fuel temperature is significant if the mass-flowrate of the input coolant flow is relatively low.